Disability and theatre a practical manual for inclusion in the arts - Barton-Farcas, Stephanie (Routledge, Taylor & Francis Group, 2018)
"A companion website contains checklist for casting, rehearsals, pre-and post-production, fillable worksheets, press and marketing examples, guidelines on how to write a successful audition call, setting up production photos, a real-time list of ADA requirements, a study guide, and example quizzes for staff."-- Publisher's description.